A resident of Deussua in the Kudd - Mumbai Archive Project (Jio Institute, 2024)
Goans emigrated to Mumbai in search of better trade, education, and employment opportunities. Erivan Velho, a 26-year-old from the village of Deussua, is staying at the club where he is preparing for his exams. The Kudd offers students like Erivan a quiet place to stay and study away from the hustle of the city.